Strategi Pengembangan Instalasi Rawat Inap Pada Rumah Sakit Hermina Pasteur - Andriani, Neneng Yanti (Jurnal Khazanah Intelektual, 2023)
This study aims to identify and analyze inpatient installation development strategies in an effort to improve service quality (Case Study at Hermina Pasteur Hospital).The results of this study are expected to contribute to increasing the ability of practitioners with regard to operational management studies and can provide input for solving problems in matters relating to management "Strategy for Development of Inpatient Installations in Efforts to Improve Service Quality at Hermina Pasteur Hospital in particular and Hospital in the city of Bandung in general. The research method used is qualitative with a single case study approach. The data collection used was interviews accompanied by observation and literature techniques. The informants used in this study really understood and mastered internal and external situations by giving several questions (interviews) related to the strategy for developing an inpatient installation. Hermina Pasteur Hospital, Bandung City. The results of the study show that the current condition of the inpatient installation is inadequate or it can be said that it is still not good. The quality of service at Hermina Pasteur Hospital from several interviews can be concluded that officers do not provide enough service to patients Keywords: Inpatient Installation Development Strategy, Service Quality